On the Group Controllability of Leader-Based Continuous-Time Multiagent Systems - Bo Liu; Licheng Wu; Rong Li; Housheng Su; Yue Han (Complexity)
The group controllability of continuous-time multiagent systems (MASs) with multiple leaders is considered in this paper, where the entire group is compartmentalized into a few subgroups. The group controllability concept of continuous-time MASs with multiple leaders is put forward, and the group controllability criteria are obtained for switching and fixed topologies, respectively. Finally, the numerical simulations are given to prove the validity of the theoretical results.